Preferensi Publik terhadap Wakaf Uang di Sumatera Barat - Adisti, Adila (AL-MUZARA'AH, 2021)
Cash waqf can be a solution in optimizing the potential of land waqf asset in Indonesia, in order to reach economic empowerment. In Indonesia, cash waqf had a great potential reaching 180 trillion rupiah, however the money acquired on 2019 only reached 400 billion rupiah. Several factors caused the low rate of accumulation of cash waqf, namely religiousity, cash waqf literacy, waqf inclusion, and waqf institution management. This study aims to find out public preference toward cash waqf specifically in West Sumatera Province. The analytical method used is PLS-SEM qualitative analysis using SmartPLS 3.9.2 as a tool. Purposive sampling technique was used to assign 175 respondents. Results showed that there are positive and significant relationship between cash waqf literacy, waqf inclusion and waqf institution management variables with the public preference towards cash waqf. Whereas religiousity factor had positive but insignificant effect to the public preference of cash waqf.